Bilateral Cooperation and Human Trafficking Eradicating Modern Slavery between the United Kingdom and Nigeria - Ikeora, May (Global Ethics, 2018)
This book presents a case study of human trafficking from Nigeria to the UK, with a focus on practical measures for ending this trafficking. The study addresses the many aspects of human trafficking, including sexual exploitation, domestic servitude, labor exploitation, benefit fraud, and organ harvesting. Despite the huge investment of the international community to eradicate it, this form of modern day slavery continues, and the author urges stakeholders to focus not only on criminals but also on attitudes, cultures, laws and policies that hinder the eradication of modern slavery. May Ikeora is an independent research consultant and the co-founder of ThinkKnowAct Initiative, which focuses on human rights and empowering women and girls. She is an Associate for Women in Sustainable Enterprise Development (WISE) and The Gender Education and Enterprise Development for Africa (GEEDA) in the UK.